Tension analysis of a 6-degree-of-freedom cable-driven parallel robot considering dynamic pulley bearing friction. (August 2017) - Choi, Sung-Hyun; Park, Jong-Oh; Park, Kyoung-Su
Recently, cable-driven parallel robots have been used in many industrial fields. Especially, cable-driven parallel robots have been used in specialized industrial fields where dynamical features such as high accuracy in systems requiring quick transitions. In this article, Dahl friction model was proposed to predict the tension during quick transitions in cable-driven parallel robots. And the Dahl friction equation for a combination of pulleys connected in series was derived. From their relationships, a modified kinematic equation was developed for redundant actuation cable-driven parallel robot systems. Because Dahl friction has non-linear characteristics, the actual tension set problem was solved using the Newton–Raphson method combined with the constrained non-linear multivariable optimal method. Finally, the tension profiles were simulated using both Dahl and Coulomb friction models with fast and slow velocities. In conclusion, according to simulation, Dahl friction model expressed dynamic characteristics such as pre-sliding in the transition range. Thus, it was in better agreement with the experiments than the Coulomb friction model. In particular, Dahl friction model was more accurate in the case of slow motion in the pre-sliding range.